Boronic esters of corannulene: potential building blocks toward icosahedral supramolecules1. Issue 6 (15th June 2015) - Da Ros, Sara; Linden, Anthony; Baldridge, Kim K.; Siegel, Jay S.
<x xml:space="preserve">Abstract</x> Direct iridium-catalyzed multi-borylation provides a valuable tool for the symmetric functionalization of various polycyclic aromatic hydrocarbons, inter alia, regular fivefold derivatization of corannulene.